The role of automation in the efficiency of B2B email marketing - Ghimire , Subekshaa (My University, 2026)
This thesis aims to explore how automation tools influence the efficiency of email marketing in B2B marketing. This thesis combines both the Resource-Based View (RBV) and the Technology Acceptance Model (TAM) as a theoretical framework. In the thesis, the theoretical framework connects email marketing automation with ease of use and competitive advantage within the organization by analysing its benefits and challenges. A qualitative research method has been chosen for the methodology in this thesis. The data has been collected through semi-structured interviews which were conducted with employees, managers, and developers from five companies with diverse backgrounds to ensure the reliability and accuracy of the findings. These case firms include companies such as wholesale, medical sector, travel agency, software, and education. In data analysis, thematic analysis was used in order to identify patterns and add themes to the analysis. The study reveals that automation plays an essential role in enhancing the efficiency of email marketing. The findings suggest automation provides numerous benefits to email marketers beyond merely improving efficiency, and contributes to the transformation of users’ roles towards strategic work. Additionally, automation helps companies in achieving competitive advantage. These findings of this study align with the literature, theoretical framework and provides various theoretical and managerial implications. It provides valuable perspectives to managers on how to gain competitive advantage through the use of email marketing automation, which can enhance revenue growth in the organization. In conclusion, the study highlights that automation is a powerful tool in the current business environment, as well as support strategic roles for employees.
Keywords: marketing; automation; email; efficiency (properties); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development